One-Pot Synthesized Amorphous Cobalt Sulfide With Enhanced Electrochemical Performance as Anodes for Lithium-Ion Batteries - Ren, Long-Long; Wang, Lin-Hui; Qin, Yu-Feng; Li, Qiang (Frontiers in Chemistry, 2022)
In order to solve the poor cycle stability and the pulverization of cobalt sulfides electrodes, a series of amorphous and crystalline cobalt sulfides were prepared by one-pot hydrothermal synthesis through controlling the reaction temperatures. Compared to the crystalline cobalt sulfide electrodes, the amorphous cobalt sulfide electrodes exhibited superior electrochemical performance. The high initial discharge and charge capacities of 2132 mAh/g and 1443 mAh/g at 200 mA/g were obtained. The reversible capacity was 1245 mAh/g after 200 cycles, which is much higher than the theoretical capacity. The specific capability was 815 mAh/g at 800 mA/g and increased to 1047 mAh/g when back to 100 mA/g, indicating the excellent rate capability. The outstanding electrochemical performance of the amorphous cobalt sulfide electrodes could result from the unique characteristics of more defects, isotropic nature, and the absence of grain boundaries for amorphous nanostructures, indicating the potential application of amorphous cobalt sulfide as anodes for lithium-ion batteries.